2004
DOI: 10.1038/oby.2004.139
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Effects of Gastric Bypass Surgery on Circulating Ghrelin Levels

Abstract: MORÍNIGO,ROSA, ROSER CASAMITJANA, VIOLETA MOIZÉ , ANTONIO M. LACY, SALVADORA DELGADO, RAMON GOMIS, AND JOSEP VIDAL. Short-term effects of gastric bypass surgery on circulating ghrelin levels. Obes Res. 2004;12:1108 -1116. Objective: To prospectively evaluate the short-term effects of Roux-en-Y gastric bypass (RYGBP) on ghrelin secretion and its relevance on food intake and body weight changes. Research Methods and Procedures: Ghrelin response to a standardized test meal was evaluated in eight obese patients (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 47 publications
(96 reference statements)
8
62
1
1
Order By: Relevance
“…This was in contrast to the blunted pattern seen in the morbidly obese group. The results in our study contrast to other studies where no meal-induced changes in ghrelin levels were found in postoperative patients, 16,17,30 and another study reported a smaller magnitude of the decline in serum ghrelin levels after oral glucose tolerance test in patients after gastric bypass surgery compared with lean subjects. 18 On the other hand, one recent study reported a similar response to a test meal in lean and RYGBP groups and higher in operated patients than in BMI-matched controls.…”
Section: Discussioncontrasting
confidence: 99%
“…This was in contrast to the blunted pattern seen in the morbidly obese group. The results in our study contrast to other studies where no meal-induced changes in ghrelin levels were found in postoperative patients, 16,17,30 and another study reported a smaller magnitude of the decline in serum ghrelin levels after oral glucose tolerance test in patients after gastric bypass surgery compared with lean subjects. 18 On the other hand, one recent study reported a similar response to a test meal in lean and RYGBP groups and higher in operated patients than in BMI-matched controls.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies in adults demonstrated increasing ghrelin levels, 12-15 stable ghrelin concentrations [16][17][18][19] and decreasing ghrelin levels in weight reduction. 20 Reduction of overweight was achieved in most of these studies by gastric surgery.…”
Section: Discussionmentioning
confidence: 99%
“…9 In obese adults and children, leptin levels have shown to be increased, while ghrelin levels are decreased. 7,[9][10][11] There are only few studies consisting of only a small number of subjects, which analyze the changes in ghrelin levels due to reduction of overweight in a time period of weeks up to months with contradictory results: four studies reported increasing ghrelin levels, [12][13][14][15] four studies no changes of ghrelin levels [16][17][18][19] and one study decreasing ghrelin levels after weight reduction. 20 Until now, there is only one study on ghrelin levels in obese children after weight reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Much is known regarding life with chronically reduced ghrelin levels because thousands of individuals have undergone Rouxen-Y gastric bypass surgery, which reduces ghrelin levels by 50-70% for weeks relative to weight-loss controls. Postsurgical ghrelin levels are even lower after total gastrectomy or sleeve gastrectomy (removal of the fundus) and remain so in the long-term (34)(35)(36)(37)(38)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77). The Roux-en-Y gastric bypass and sleeve gastrectomy surgeries both produce massive weight reduction, greater than those of other surgical procedures that less effectively reduce ghrelin levels and improve the health of previously morbidly obese patients with low complication rates (37,78,79).…”
Section: Resultsmentioning
confidence: 99%